Pengaruh Financial Leverage, Net Profit Margin, Dividend Payout Ratio Terhadap Praktik Perataan Laba pada Perusahaan Industri Dasar dan Kimia - Sinta Trisnawati; Vinus Maulina; Riril Mardiana Firdaus (Jurnal Riset Mahasiswa Manajemen, 2019)
This study aims to determine the effect of Financial Leverage, Net Profit Margin, Dividend Payout Ratio on income smoothing practices in basic and chemical industrial companies on the Indonesia Stock Exchange for the period 2013-2017. This type of research is quantitative research. The sample of this study is the financial statements of 29 companies listed on the Stock Exchange in the 2013-2017 period. The sampling technique used in this study is the purposive sampling method, which is a sampling technique with certain considerations that are based on research interests. The data used is secondary data in the form of company financial statements obtained from www.idx.co.id. The data analysis technique used in this study is binary logistic regression analysis. The results of this study indicate that partially Financial Leverage, Net Profit Margin, significantly influence the practice of income smoothing. Whereas Dividend Payout Ratio does not have a significant effect on income smoothing practices.